Virtue Ethics: Analysing emotions in a police interview with a crime suspect - Crowley, Michael (Policing, 2012)
Justice goes some way to being served when statements from police interviews with suspects are admissible as evidence in court. Admissible evidence confirms that the police have worked within legal constraints and satisfied universal ethical principles that appear in the police code of conduct. Conversely, when police behave improperly and an accused person walks free, police authorities have needed to placate an outraged public by promising reforms. This article explores sections of Arthurs’ case to illustrate differences between legal and illegal police conduct when interviewing a murder suspect. Parts of the interview were admissible as legal evidence; the majority was not. This article then considers the practical relevance of ethical constraints formalized as universal moral principles in the police code of conduct. It suggests that Aristotle’s virtue ethics may be a more appropriate ethical response than referring to abstract moral principles in analysing police/suspect interviews. The article concludes by calling for police to include virtue ethics as part of conversation management strategies when analysing police/suspect interviews